2015
DOI: 10.1002/jmv.24076
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of human cosaviruses in Tunisia, North Africa

Abstract: A new picornavirus, named human Cosavirus (HCoSV) was isolated recently from stools of children with acute flaccid paralysis (AFP) and healthy children in Pakistan and Afghanistan. Since then, it was also isolated from patients from other countries. Five species are presently identified forming a new genus in the Picornaviridae family. This study reports the detection of HCoSV in stool specimens collected as part of the National Poliovirus surveillance Program in Tunisia, between 2011 and 2012, from patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 11 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…Our data showed that the detection rate of CosV in diarrheal children (1%) was lower than observed in China or Brazil, where they were reported in diarrheal children in 2.8% and 3.6% of patients [ 33 , 34 ] , respectively. CosV has been previously reported in up to 33.0% of healthy Tunisian subjects or suffering from non-polio acute flaccid paralysis, most of them being children <6 years old [ 35 ] . However, the difference in detection rates is due to different natures of the two cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Our data showed that the detection rate of CosV in diarrheal children (1%) was lower than observed in China or Brazil, where they were reported in diarrheal children in 2.8% and 3.6% of patients [ 33 , 34 ] , respectively. CosV has been previously reported in up to 33.0% of healthy Tunisian subjects or suffering from non-polio acute flaccid paralysis, most of them being children <6 years old [ 35 ] . However, the difference in detection rates is due to different natures of the two cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Since cosaviruses have been detected in both healthy and symptomatic individuals and case-cohort studies are still missing, the etiological role remains unclear. To determine whether cosaviruses are the causative agents of neurological or gastrointestinal disorders or act as bystanders needs further investigation [43,44].…”
Section: Discussionmentioning
confidence: 99%
“…These three novel viruses were isolated from patients with different clinical and epidemiologic patterns ( 4 ). They were isolated from patients with GE ( 6 , 16 ) and neurological disorders ( 17 19 ). While GE is a threat to global health, the causative agents of many cases still remained unclear ( 4 ).…”
Section: Introductionmentioning
confidence: 99%